PROBLEM-BASED LEARNING FOR TEACHING WRITING OF DESCRIPTIVE TEXT TO EFL STUDENTS WITH PERSONALITY TRAITS: INTROVERSION AND EXTROVERSION (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Problem-based learning (PBL) provides a number of potential language learning benefits through opportunities forauthentic meaningful language use. Previous researches have also showed how PBL can generate students ’ idea and developtheir writing skill independently. The aim of this study was to provide more conclusive results in the area of the relationshipbetween extroversion and introversion and language performance in English as a Foreign Language (EFL) environment. Thedata was taken from pretest and posttest. There were 40 participants from one class of the fourth semester students of EnglishDepartment who attended Genre Based Writing class taken by using purposive sampling. The research was conducted atEnglish department of University of Sultan Ageng Tirtayasa, Banten. The main outcome of this research was to triggerstudents’ idea in order they could express their thought in the written form. Result indicated that through PBL, both introvertand extrovert students had better result in writing descriptive. Hence, it can be concluded that applying PBL as the method isnecessary to trigger students’ idea for having writing product. It is because writing skill requires self-knowledge to express thethought process. Thus, students can experience the combination between process and product.